Does the presence of an implant including expander with internal port alter radiation dose? An ex vivo model. Issue 1 (March 2013) - Strang, Barbara; Murphy, Kyla; Seal, Shane; Dal Cin, Arianna
Background: There is a lack of literature examining the dosimetric implications of irradiating breast implants and expanders with internal ports inserted at the time of mastectomy. Objective: To determine whether the presence of breast expanders with port in saline or silicone implants affect the dose uniformity across the breast when irradiated with various photon and electron energies. Methods: One tissue-equivalent torso phantom with overlying tissue expanders in saline or silicone implants were irradiated using tangential fields with 6 MV and 18 MV photons and 9 MeV and 12 MeV electrons. All dose measurements were performed using thermoluminescent dosimeters (TLDs). The TLDs were arranged around the port and the perimeters of either the expander, or saline or silicone implant. Comparisons of measured radiation doses, and between the expected and measured doses of radiation from the TLDs on each prosthesis, were performed. Data were analyzed using two-tailed t tests. Results: There were no differences in TLD measurements between the expander and the saline implant for all energy modalities, and for the expected versus actual measurements for the saline implant. Higher than anticipated measurements were recorded for a significant number of TLD positions around the silicone implants. Conclusions: Radiation doses around saline implants or expanders with internal port were unaltered, whereas dose recordings for silicone implants were higher than predicted in the present laboratory/ex vivo study.